Pattern of malocclusion among orthodontic patients in East Coast of Sabah - Lee, Jin Han; Lillybia Emily Ebin (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study reviewed the pattern of malocclusion among orthodontic patients in East Coast of Sabah and the type of treatment indicated for the patients. A total of 138 pre-treatment orthodontic records of patients who attended the orthodontic consultation clinic in year 2018 were included in this cross-sectional retrospective study. Data taken were demographic data, source of referral, BSI (British Standards Institutes) incisor classification, skeletal pattern, and type of treatment. All data were analysed descriptively using Stata 15. Based on the results, mean age of the patients was 16.89 ± 0.37 years. More females sought orthodontic treatment (n=101, 73.19%) than males. Majority of the patients were Chinese (n=68, 49.28%) and Bumiputera Sabah (n=55, 39.86%). Main source of referral was from dental officers (n=128, 92.75%). The distribution of malocclusion showed high percentage of Class II Division 1 (n=56, 40.58%), followed by Class III (n=45, 32.61%), Class I (n=34, 24.64%) and Class II Division 2 (n=3, 2.17%). For skeletal pattern, more patients presented with Class II (n=54, 39.13%), while the number of patients presented with Class I and Class III were equal (n=42, 30.43%). Class III malocclusion (n=29, 42.65%) and Class III skeletal pattern (n=29, 42.65%) were more common in Chinese patients. Treatment indicated was mostly fixed orthodontic appliance (n=120, 86.96%). In conclusion, Class II Division 1 malocclusion and Class II skeletal pattern were most common among the patients. Class III malocclusion and Class III skeletal pattern were typical features among the Chinese patients. Fixed orthodontic appliance was the most common treatment method.